2020
DOI: 10.1002/mrd.23315
|View full text |Cite
|
Sign up to set email alerts
|

Combined use of dbcAMP and IBMX minimizes the damage induced by a long‐term artificial meiotic arrest in mouse germinal vesicle oocytes

Abstract: Phosphodiesterase (PDE)‐mediated reduction of cyclic adenosine monophosphate (cAMP) activity can initiate germinal vesicle (GV) breakdown in mammalian oocytes. It is crucial to maintain oocytes at the GV stage for a long period to analyze meiotic resumption in vitro. Meiotic resumption can be reversibly inhibited in isolated oocytes by cAMP modulator forskolin, cAMP analog dibutyryl cAMP (dbcAMP), or PDE inhibitors, milrinone (Mil), Cilostazol (CLZ), and 3‐isobutyl‐1‐methylxanthine (IBMX). However, these chemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it has been reported that forskolin supplemented to the pre‐maturation medium in bovine and pigs can increase oocyte cAMP levels (Park, Lee, et al., 2016), decrease intra‐oocyte H 2 O 2 and increase intra‐oocyte glutathione and maintain meiotic arrest (Leal et al., 2019). A high level of forskolin in the culture medium produced a superior apoptosis rate, leading to lower quality of oocytes (Wu et al., 2020). These data concur with a prior work screening that a high dose of forskolin triggered cellular apoptosis and DNA damage (Paschoal et al., 2016).…”
Section: Impacts Of Forskolin On In Vitro Oocyte Maturationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been reported that forskolin supplemented to the pre‐maturation medium in bovine and pigs can increase oocyte cAMP levels (Park, Lee, et al., 2016), decrease intra‐oocyte H 2 O 2 and increase intra‐oocyte glutathione and maintain meiotic arrest (Leal et al., 2019). A high level of forskolin in the culture medium produced a superior apoptosis rate, leading to lower quality of oocytes (Wu et al., 2020). These data concur with a prior work screening that a high dose of forskolin triggered cellular apoptosis and DNA damage (Paschoal et al., 2016).…”
Section: Impacts Of Forskolin On In Vitro Oocyte Maturationmentioning
confidence: 99%
“…These data concur with a prior work screening that a high dose of forskolin triggered cellular apoptosis and DNA damage (Paschoal et al., 2016). An increase of cAMP synthesis in the cytoplasm may lead to a consistent with boosting the mitochondrial function in oocyte (Wu et al., 2020). Previously, it was evidenced that the appropriate level of forskolin could maintain the stability of DNA integrity in the cell and reduced the DNA damage in oocytes (Paschoal et al., 2016).…”
Section: Impacts Of Forskolin On In Vitro Oocyte Maturationmentioning
confidence: 99%